2018
DOI: 10.3389/fchem.2018.00537
|View full text |Cite
|
Sign up to set email alerts
|

A Chiral Bipyrimidine-Bridged Dy2 SMM: A Comparative Experimental and Theoretical Study of the Correlation Between the Distortion of the DyO6N2 Coordination Sphere and the Anisotropy Barrier

Abstract: Chiral bipyrimidine-bridged dinuclear LnIII complexes of general formula [(μ-bipym){((+)-tfacam)3Ln}2] and [(μ-bipym){((-)-tfacam)3Ln}2], have been prepared from the assembly of Ln(AcO)3·nH2O (LnIII = Dy, Gd), (+)/(−)-3-(trifluoroacetyl)camphor enantiopure ligands ((+)/(-)-Htfacam) and bipyrimidine (bipym). The structure and chirality of these complexes have been supported by single-crystal X-Ray diffraction and circular dichroism. The study of the magnetic properties of the GdIII complexes revealed a very wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 145 publications
2
22
0
Order By: Relevance
“…The best fit was obtained for τ 0 = 3.2(7) × 10 −6 s and ∆ = 53(2) K parameters which are used to simultaneously fit the log(τ) vs. T plots at 0 Oe and 1200 Oe with shared Raman parameters and additional QTM process in zero fields. It is worth noticing that this effective energy barrier is close to the value of 55.1 K found in a similar dinuclear complex involving the simple 2,2 bipyrimidine bridging ligand instead of L [78]. The best simultaneous fit was obtained for τ 0 = 3.2 × 10 −6 s (fixed) and ∆ = 53 K (fixed), C = 0.10(2) s −1 K −n with n = 3.94 (15) and τ TI = 1.30(8) × 10 −4 s (Figure S24).…”
Section: Magnetic Propertiessupporting
confidence: 80%
“…The best fit was obtained for τ 0 = 3.2(7) × 10 −6 s and ∆ = 53(2) K parameters which are used to simultaneously fit the log(τ) vs. T plots at 0 Oe and 1200 Oe with shared Raman parameters and additional QTM process in zero fields. It is worth noticing that this effective energy barrier is close to the value of 55.1 K found in a similar dinuclear complex involving the simple 2,2 bipyrimidine bridging ligand instead of L [78]. The best simultaneous fit was obtained for τ 0 = 3.2 × 10 −6 s (fixed) and ∆ = 53 K (fixed), C = 0.10(2) s −1 K −n with n = 3.94 (15) and τ TI = 1.30(8) × 10 −4 s (Figure S24).…”
Section: Magnetic Propertiessupporting
confidence: 80%
“…Recent research has shown that 6-chloro-2-hydroxypyridine can be used as the bridging ligand or as the terminal ligand for assembling 3d–4f SMMs. , We chose 6-chloro-2-hydroxypyridine as the coligand to evaluate its ability for bridging lanthanide (III) ions, while the chiral β-diketone ligand (−)/(+)-3-trifluoroacetyl camphor was responsible for the introduction of chirality. When 6-chloro-2-hydroxypyridine and (−)/(+)-3-trifluoroacetyl camphor were treated with Dy­(Ac) 3 ·4H 2 O in MeOH–MeCN–H 2 O solution at room temperature in the presence of potassium tert -butoxide, the homochiral Dy­(III) dinuclear complexes [Dy 2 ( l -tfc) 4 (chp) 2 (MeOH) 2 ] ( l - 1 ) and [Dy 2 ( d -tfc) 4 (chp) 2 (MeOH) 2 ] ( d - 1 ) could be obtained. Their purity could be confirmed by comparing their XRD spectra with the simulated diffraction patterns according to their single crystal structures (Figures S1 and S2), and the corresponding peaks coincide with each other well for both l - 1 and d - 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Comparably, the bridging ligand used in another pair of enantiomerically pure Dy 2 complexes of (+)/(−)-3-trifluoroacetyl camphor, [(μ-bipym)­{((+)/(−)-tfc) 3 Dy} 2 ], is the electrically neutral [N 4 ] tetradentate ligand, bipyrimidine (bipym), and their coordination configuration is the DyN 2 O 6 square antiprism.…”
Section: Resultsmentioning
confidence: 99%
“…For mononuclear heteroleptic (LPOM + auxiliary ligand) Ln III [3,52,53] The dynamic properties of the first Dy III compound were studied under an applied dc field of 2000 kG, with the best fit parameters of U eff = 36.4 cm À 1 , τ 0 = 5.3 × 10 À 9 s, τ QTM = 0.021 s, A = 8.61 s À 1 K À 1 , n = 3.65 and C = 0.997 K À n s À 1 (Figure 7). [52] The Ln III ion have SAPR geometry like its inorganic analogue [Dy III (PW 11 O 39 ) 2 ] 11À .…”
Section: Dynamic (Ac) Magnetic Propertiesmentioning
confidence: 99%
“…This means that the ligand defines the coordination and symmetry of the complex, so the combination of different types of ligands should have an effect on the geometry that the Ln III ion will adopt. [2,3] Ln III complexes usually formed compounds with high coordination number with weak metal-ligand bonds. In the literature it is possible to find systems in which the coordination number varying from 6 to 12.…”
Section: Introductionmentioning
confidence: 99%